2020
DOI: 10.3389/fphys.2020.00593
|View full text |Cite
|
Sign up to set email alerts
|

Human Umbilical Cord Mesenchymal Stem Cell Differentiation Into Odontoblast-Like Cells and Endothelial Cells: A Potential Cell Source for Dental Pulp Tissue Engineering

Abstract: Objectives: Dental pulp regeneration is considered an ideal approach for treating dental pulp disease. Because pulp is composed of various cells, determining the proper seed cells is critical. We explored the potential of human umbilical cord mesenchymal stem cells (hUCMSCs) as seed cells for dental pulp regeneration. Methods: Liquid extract of human treated dentin matrix (LE-TDM) was acquired to culture hUCMSCs. Odontoblast-specific markers were detected by western blot, qRT-PCR, and immunofluorescence assays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…We considered that HA improved ECFCs viability through miR-139-5p in the HA-MSC-ECFC co-culture system. Generally, MSC could directional differentiated into endothelial cells in the medium supplemented with cytokines ( Wang et al, 2018 ; Zhang et al, 2020 ) and miRs participate in the process ( Arderiu et al, 2019 ). Decreased miR-139-5p expression in CD31 positive cells induced by HA may regulate target genes expression such as increased expression of VEGF and PDGF, which may further induced endothelial differentiation and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…We considered that HA improved ECFCs viability through miR-139-5p in the HA-MSC-ECFC co-culture system. Generally, MSC could directional differentiated into endothelial cells in the medium supplemented with cytokines ( Wang et al, 2018 ; Zhang et al, 2020 ) and miRs participate in the process ( Arderiu et al, 2019 ). Decreased miR-139-5p expression in CD31 positive cells induced by HA may regulate target genes expression such as increased expression of VEGF and PDGF, which may further induced endothelial differentiation and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, stem cell-based therapies would be an improving approach to repair or replace the damaged or lost tissues of teeth in order to recover the morphological and biological functions [ 204 ]. Recently, it was shown that UC-MSC possess the ability to differentiate into odontoblast-like cells under the microenvironment induced by a liquid extract of human treated dentin matrix in vitro [ 205 ]. On the other hand, we consider the possibility that MSC secretome-derived products, such as conditioned medium and/or exosomes, may be a new strategy to induce dental stem cells to dent pulp regeneration, which will require further well-designed investigation.…”
Section: New Horizons For Clinical Applications Of Mscmentioning
confidence: 99%
“…The differentiation and proliferation of stem cells is influenced by the microenvironment, also called the “stem cell niche” [ 21 ]. Most recently, a study revealed that hUCMSCs could differentiate into odontoblast-like cell via human dentin matrix [ 22 ]. The inserted adipose tissue also underwent neoadipogenesis, which was potentially driven by the stem cell and native adipose extracellular matrix.…”
Section: Introductionmentioning
confidence: 99%